Analysis of transitional stresses in non-local thermo-elastic disc under steady-state temperature - Ailawalia, Praveen; Kaur, Jatinder; Kumar, A.; Jurczak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
In solid mechanics, there are various applications of non-local theories in wave propagation, size effects, surface effects, and understanding interactions of composite materials. There are certain parameters associated with rigid bodies like stress, angular speed, and displacement which show variation with changes in temperature, thickness, density, and media.
Keywords: non-local media; rotation; disc; thickness; temperature variation; angular speed